Language Modulates Categorical Effects of Moving Color Objects. (March 2022) - Sun, Mengdan; Zhang, Xuemin
Categorical perception (CP) of color claims that colors from different linguistic categories are discriminated more easily than those from the same category, suggesting that language may interact with visual perception. However, controversy remains regarding whether CP effects derive from language. Recently, CP effects were found in a dynamic paradigm named multiple object tracking (MOT). Here, we investigated whether this kind of CP is dependent on online use of language. We found that the CP effects are reduced by verbal interference when the participants were required to memorize color words during tracking (Experiment 2) but not when the interference stimuli were digits (Experiment 1). Our study suggested that the CP effects in tracking depend partly on online use of language and that the difficulty of verbal interference tasks influences the capability of disrupting CP.